Thyroid Cancer and Benign Nodules After Exposure In Utero to Fallout From Chernobyl - Hatch, Maureen; Brenner, Alina V; Cahoon, Elizabeth K; Drozdovitch, Vladimir; Little, Mark P; Bogdanova, Tatiana; Shpak, Victor; Bolshova, Elena; Zamotayeva, Galyna; Terekhova, Galyna; Shelkovoy, Evgeniy; Klochkova, Viktoria; et al. (The journal of clinical endocrinology and metabolism, 2019)
Abstract Background Children and adolescents exposed to radioactive iodine-131 (I-131) in fallout from the 1986 Chernobyl nuclear accident appear to be at increased risk of thyroid cancer and benign thyroid nodules. The prenatal period is also considered radiosensitive, and the fetal thyroid can absorb I-131 from the maternal circulation. Objectives We aimed to estimate the risk of malignant and benign thyroid nodules in individuals exposed prenatally. Methods We studied a cohort of 2582 subjects in Ukraine with estimates of I-131 prenatal thyroid dose (mean = 72.6 mGy), who underwent two standardized thyroid screening examinations. To evaluate the dose-response relationship, we estimated the excess OR (EOR) using logistic regression. Results Based on a combined total of eight cases diagnosed at screenings from 2003 to 2006 and 2012 to 2015, we found a markedly elevated, albeit not statistically significant, dose-related risk of thyroid cancer (EOR/Gy = 3.91, 95% CI: –1.49, 65.66). At cycle 2 (n = 1,786), there was a strong and significant association between I-131 thyroid dose and screen-detected large benign nodules (≥10 mm) (EOR/Gy = 4.19, 95% CI: 0.68, 11.62; P = 0.009), but no significant increase in risk for small nodules (<10 mm) (EOR/Gy = 0.34, 95% CI: –0.67, 2.24; P = 0.604). Conclusions The dose effect by nodule size, with I-131 risk for large but not small nodules, is similar to that among exposed children and adolescents in Belarus. Based on a small number of cases, there is also a suggestive effect of I-131 dose on thyroid cancer risk. We studied a cohort in Ukraine exposed prenatally to I-131 in fallout from Chernobyl and found a suggestive increase in thyroid cancer and a significant association with risk of large benign nodules.